Berberine Damages the Cell Surface of Methicillin-Resistant Staphylococcus aureus - Zhang, Xiujuan; Sun, Xiaoying; Wu, Jiaxin; Wu, Yue; Wang, Yali; Hu, Xiaoqing; Wang, Xiaoyuan (Frontiers in Microbiology, 2020)
Methicillin-resistant Staphylococcus aureus (MRSA) is currently regarded as one of the most important drug-resistant pathogens causing nosocomial and community-acquired infections. Although berberine (BER) has shown anti-MRSA activity, the underlying mechanism is still unclear. In this study, the damage caused by BER on the cell surface of MRSA was systematically investigated by performing BER susceptibility test, determining K+ and alkaline phosphatase (ALP) release, detecting morphological alterations using scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and ascertaining lipid profiles. The results showed that the minimum inhibition concentration (MIC) of BER against MRSA252 was 128 µg/mL. Under the sub-MIC doses of BER, cell membrane permeability gradually increased in a dose-dependent manner, and 1 × MIC led to 43.8% higher K+ leakage and 4-fold higher ALP secretion. The injuries on MRSA cell surface were further verified by SEM and TEM, and some cells displayed a doughnut-shaped structure. BER significantly altered the fatty acids species contents, including saturated fatty acids (C14:0, C15:0, C16:0, C18:0, and C20:0), and unsaturated fatty acids (C20:4, C20:1, and C18:1), indicating that BER compromised cell membrane integrity via lipid fluctuation. Thus, the findings of this study could help to unravel the molecular mechanism of BER against MRSA.